Phenolic content and antioxidant activity of Hibiscus cannabinus L. seed extracts after sequential solvent extraction - Noordin, Mohd Yusri; Chan, Kim Wei; Iqbal, Shahid; Ismail, Maznah (MDPI, 2012)
A sequential solvent extraction scheme was employed for the extraction of antioxidant compounds from kenaf (Hibiscus cannabinus L.) seeds. Yield of extracts varied widely among the solvents and was the highest for hexane extract (16.6% based on dry weight basis), while water extract exhibited the highest total phenolic content (18.78 mg GAE/g extract), total flavonoid content (2.49 mg RE/g extract), and antioxidant activities (p < 0.05). DPPH and hydroxyl radical scavenging, β-carotene bleaching, metal chelating activity, ferric thiocyanate and thiobarbituric acid reactive substances assays were employed to comprehensively assess the antioxidant potential of different solvent extracts prepared sequentially. Besides water, methanolic extract also exhibited high retardation towards the formation of hydroperoxides and thiobarbituric acid reactive substances in the total antioxidant activity tests (p < 0.05). As conclusion, water and methanol extracts of kenaf seed may potentially serve as new sources of antioxidants for food and nutraceutical applications.